An exploratory proposal of the professional profile in tourism from Limón, Costa Rica (201 - Espinoza Vargas, Cherry (2019)
The following research arises from the lack of current studies conducted in Costa Rica and the province of Limon itself, which refers to the preparation of professionals for the tourism sector. The objective of the following investigation gives answer to which is the professional profile that is required to respond to the current and future necessities of the tourism sector, where variables will be offered, knowledge, abilities and attitudes will be identified in order to formulate the professional profile according to the province. In order to base this work, we proceed to the extraction and bibliographic revision, besides a mapping and a method that will define concepts and theories of tourism, professional profile, giving to the investigation a qualitative approach and an ethnographic investigation. The work presents contributions from various professional areas, academic degree, education, local government sector, business sector, graduates of the Sustainable Tourism Management career, which gave important and different perspectives, to provide a proposal for the professional profile of Tourism for the Central district of Limon.